Production of interferon-γ by natural killer cells and aging in chronic human schistosomiasis. Issue 5 (2004) - Speziali, E.; Bethony, J.; Martins-Filho, O.; Fraga, L. A. O.; Lemos, D. S.; Souza, L. J.; Correa-Oliveira, R.; Faria, A. M. C.
Abstract : BACKGROUNG : Aging is associated with several alterations in the phenotype, repertoire and activation status of lymphocytes as well as in the cytokine profile produced by these cells. As a lifelong condition, chronic parasitic diseases such as human schistosomiasis overlaps with the aging process and no systematic study has yet addressed the changes in immune response during infection with Schistosoma mansoni in older individuals. Aim : Herein we study the influence of immunological alterations brought about by senescence in the course of schistosomiasis. Materials and methods : Individuals 10-95 years of age, from both sexes, from an endemic area for S. mansoni infection were matched by intensity of infection as measured by egg counts. We analyzed, as a parameter, cytokine expression by lymphocytes and natural killer cells after in vitro stimulation with soluble egg antigen and soluble worm antigen using flow cytometry. Results : We demonstrated that the frequency of CD16 + interferon-γ (IFN-γ) + natural killer cells in negative individuals over the age of 70 years is significantly higher than in positive individuals after in vitro stimulation with S. mansoni antigen extracts. The frequency of these cells is increased in all individuals over the age of 50 years and only declines in positive individuals after 70 years of age. Analysis of either CD4 ? or CD8 ? cells after antigen stimulation show no significant increase in frequency of IFN-γ in negative or in positive individuals of this age group, suggesting that the effect on CD16 + cells is not T-cell dependent. Conclusion : Since production of IFN-γ has been related to resistance to schistosome infection, our data suggest that age-associated changes in CD16 + cells may play a role in controlling infection intensity in the elderly in S. mansoni endemic areas of Brazil.